The Soul of The State of The Democratic Republic of Timor-Leste - Lucia de Canossa Silva Hau (Sociological Jurisprudence Journal, 2023)
The Constitution of the Democratic Republic of Timor-Leste (RDTL) was born from the womb and soul of the Maubere people which flows in the veins and body of the nation of Timor-Leste through the lyrics and national anthem (Pátria-Pátria) and describes the identity of the ideals of the Maubere homeland. The basic values embodied in the face of the RDTL constitution from the soul of the state are contained in the preamble to the constitution as an embryo for realizing the ideas and notions of the state or staatfundamentalnorm. This anthem is only sung in the Portuguese version and there is no Tetun version, which is one of the national languages of Timor-Leste. So, the law for me, like music for anyone who understands the lyrics will also understand the meaning of the music. Similar to the law that was born from the womb and the soul of the Maubere people which flows in the veins and body of the nation of Timor-Leste through lyrics and national anthem (Pátria-Pátria), which describe the identity of the ideals of the Maubere homeland.